Ultra-Fine Grinding of Minerals Using Highpressure Liquid Jet Technology - Marian Mazurkiewicz; Christopher Davey; Peter Kanjorski; Dana Hankey; Yvonne Spooner (International Mineral Processing Congress, 2003)
The concept of a high pressure liquid jet mill with highly unsteady flow, has been developed and recently patented by Cornerstone Technologies LLC (CsT), for the purpose of micron and sub-micron particle production. The mill accepts feed sizes up to 15mm for some materials and is capable of submicron production. Successful material range from precious metals such as silver and palladium to dielectric components and substrates such as Barium Titanate slips, zirconia, titania and silica. The process has also succeeded in adequately reducing the size of materials for both composite and coating uses such as anthracite coal, graphite, chrome metal, wollastonite and more than 100 others. A unique design approach has been taken to highly maximize the energy flux in the mill's chambers to create extremely high turbulence and destructive cavitation. This is assisted by shock waves, which cause particles to undergo ultra high frequency pressure pulsations, high frequency collisions and then abrasion, shattering, hydrowedging, and cleaving. Due to these extreme properties the processing occurs in just fractions of a second allowing throughputs up to 1000 kg/h on a machine that would fit inside a 60 cm box. The technical solution and technological advance, as well as the environmental and economic benefits indicate rapid and wide spread acceptance of high-pressure liquid jet milling in modern industry.